Salīdzinoša analīze par privāto un publisko mākoņu krātuves lietošanu: veiktspēja, drošība un izmaksu faktori maziem uzņēmumiem vai mājsaimniecībām - Jansons, Alberts Jēkabs (Latvijas Universitāte, 2024)
Mūsdienu digitālajā laikmetā efektīva datu glabāšana ir būtiska gan maziem uzņēmumiem, gan privātpersonām. Izvēle starp privāto (iekšējo) un publisko mākoņkrātuvi var būt sarežģīta – katram risinājumam ir savi plusi un mīnusi. Šis bakalaura darbs sniedz padziļinātu salīdzinošo analīzi, lai palīdzētu maziem uzņēmumiem un mājsaimniecībām Latvijā pieņemt informētus lēmumus par piemērotāko datu glabāšanas stratēģiju. Darbā tiek izmantota jaukta pieeja, kas apvieno gan teorētisko izpēti, gan praktiskus testus. Salīdzināsim privāto NAS ierīci (Synology DS923+) ar populāriem publiskās mākoņkrātuves pakalpojumu sniedzējiem – Google Drive, Microsoft OneDrive un Dropbox. Šajā darbā tiks veikti detalizēti veiktspējas testi, izvērtējot dažāda veida un izmēra failu augšupielādes un lejupielādes ātrumus gan lokālajā tīklā, gan izmantojot attālināto piekļuvi. Tāpat rūpīgi tiks analizēta NAS un mākoņkrātuves risinājumu izmaksu atšķirības ilgtermiņā. Šis pētījums koncentrēsies uz trim būtiskiem aspektiem. Pirmkārt, cik ātri un ērti var piekļūt datiem – veiktspējas salīdzinājums ir īpaši svarīgs, ja uzņēmuma darbībai svarīgu lomu spēlē laiks, kas nepieciešams, lai piekļūtu glabājamajiem datiem, it īpaši ja strādā ar lielāka izmēra failiem. Otrkārt, drošības jautājums – privātie NAS risinājumi piedāvā lielāku kontroli pār datiem, taču prasa arī lietotāja atbildību, savukārt mākoņkrātuvē drošību nodrošina pakalpojuma sniedzējs. Visbeidzot, šis darbs salīdzinās NAS izmaksas ar publisko mākoņkrātuves pakalpojumu sniedzējiem un noskaidros no kāda datu apjoma glabāšanas ar un bez datu dublēšanas NAS paliek financiāli izdevīgāks kā publisko mākoņkrātuves pakalpojums. Pētījuma rezultāti var sniegt vērtīgus ieteikumus Latvijas iedzīvotājiem un uzņēmumiem, palīdzot izvēlēties savām vajadzībām atbilstošāko un izdevīgāko datu glabāšanas risinājumu. Atslēgas vārdi: mākoņkrātuve, tīkla disks (NAS), veiktspēja, izmaksas, drošība, datu dublēšana, Latvija

As the demand for efficient data storage solutions continues to grow, small businesses and households face the challenge of choosing between private (on-premises) and public cloud storage deployments. Despite the extensive coverage of cloud computing in academic literature, there is a lack of comprehensive comparative analyses that consider performance, security, and cost factors. This bachelor thesis aims to bridge the research gap by conducting a comparative analysis of private (on-premises) and public cloud storage deployments, focusing on performance, security, and cost factors relevant for small businesses and households. The study seeks to guide small businesses and individual users in making informed choices about storage options. The research employs a mixed-method approach, integrating academic and non- academic sources to provide a complete view. The author conducts hands-on performance tests comparing a Synology DS923+ Network Attached Storage (NAS) device with three public cloud storage providers: Google Drive, Microsoft OneDrive, and Dropbox. The tests measure download and upload speeds for various file types and sizes across two different networks. A cost comparison is also performed between the NAS and cloud storage solutions. The performance tests reveal that the Synology DS923+ NAS outperforms all cloud storage providers on a local network, with Dropbox being the closest competitor. When accessed remotely, the NAS remains competitive, surpassing Google Drive and Microsoft OneDrive and only slightly trailing behind Dropbox. The cost analysis indicates that a NAS solution becomes more cost-effective than cloud storage when storing at least 2TB of data without redundancy or 3TB with redundancy, with break-even periods of approximately 20 and 24 months, respectively. The results provide valuable insights for small businesses and households considering public and private cloud storage solutions. The study highlights the optimal storage choices based on factors such as performance requirements, data redundancy needs, and cost- effectiveness. It also identifies the strengths and weaknesses of different RAID configurations and cloud storage providers in various scenarios. The research faced limitations, including a limited geographical scope for performance testing, the absence of multi-user scenarios, and the exclusion of potential internet connectivity cost changes based on the chosen storage solution. These limitations provide opportunities for future research to refine the accuracy and comprehensiveness of the findings. Future studies could expand the performance testing scope to include international locations, investigate the impact of multiple simultaneous users on NAS and cloud solutions, and consider the potential cost implications of internet connectivity changes based on the chosen storage solution. Additionally, researchers could explore the ease and flexibility of scaling storage up or down, which favors cloud providers, and its impact on the overall cost analysis. Keywords: cloud storage, Network Attached Storage (NAS), performance, cost, security
A Comparative Analysis of Private (on-premises) and Public Cloud Storage Deployments: Performance, Security, and Cost Factors for small businesses or households
Keywords: Datorzinātne